Psycholinguistic Basis for the Intensification of Foreign Language Teaching in Non-Linguistic Directions - Kholoqova Khafiza Vokhidovna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Within the framework of this article, we tried to present a description of the ways of possible psychological activation of foreign language teaching, which can influence the result of acquiring a foreign language and the ways of its implementation in the educational process in non-linguistic institutions. In analyzing this study, we suggested some planned activities that greatly helped foreign language learners to increase their ability to learn the target language and at the same time can also encourage second foreign language teachers to find the best way for their learning. Since the psycholinguistic approach to teaching a foreign language implies a constitutional basis for determining specific psychological directions and principles for organizing language teaching, separate functions of professional linguistic material and language activities. An analysis of psychological and pedagogical studies of the intensification of professionally oriented foreign language teaching in non-linguistic institutions shows that this problem is psychological and pedagogical, since it requires taking into account both psychological factors and personal characteristics (motivation, readiness to learn a foreign language, activity, independence, development and etc.) and the need for a specially organized, purposeful pedagogical process, which includes psychological approaches, principles, organizational and pedagogical conditions, methods and means for realizing the goals and objectives of oriented education in the specialization of the future profession.